Reduced Responsiveness to Volatile Signals Creates a Modular Reward Provisioning in an Obligate Food-for-Protection Mutualism - Hernández-Zepeda, Omar F.; Razo-Belman, Rosario; Heil, Martin (Frontiers in Plant Science, 2018)
Plants in more than 100 families secrete extrafloral nectar (EFN) to establish food-for-protection mutualisms with ants. Facultative ant-plants secrete EFN as a jasmonic acid (JA)-dependent response to attract generalist ants, whereas obligate ant-plants like the Central American 'Swollen-Thorn Acacias' host colonies of specialized ants. Nevertheless, an individual host can carry ant colonies from different species. We reasoned that hosts that associate simultaneously with various partners should produce rewards in a modular manner to preferentially reward high quality partners. To test this hypothesis, we applied JA to distinct leaves and quantified cell wall invertase activity (CWIN; a regulator of nectar secretion) and EFN secretion by these 'local' (i.e., treated) and the 'systemic' (i.e., non-treated) leaves of the same branch. Both CWIN activity and EFN secretion increased in local and systemic leaves of the facultative ant-plant Acacia cochliacantha, but only in the local leaves of the obligate ant-plant, A. cornigera. The systemic EFN secretion in A. cochliacantha was associated with an enhanced emission of volatile organic compounds (VOCs). In other plants, VOCs function as 'external signals' that control systemic defence responses. Indeed, EFN secretion in A. cochliacantha as well as A. cornigera was induced by the headspace of JA-treated branches of A. cochliacantha, but not A. cornigera, and GC-MS analyses identified six VOCs in the headspace of A. cochliacantha that were not emitted by A. cornigera. Among these VOCs, β-caryophyllene and (cis)-hexenyl isovalerate have already been reported to induce defence traits in other species, including EFN secretion. Our observations show that the modular rewarding in A. cornigera is likely to result from a reduced emission of the systemic signal – rather than from a reduced responsiveness to the signal. We suggest that modular rewarding allows hosts to restrict the metabolic investment to specific partners and to efficiently 'sanction' of non-reciprocating exploiters.